International Expansion of Basketball Organizations through Esports - Abromavičius, Edgaras; Čingienė, Vilma (Information & Media, 2025)
This article explores the international expansion of sports organizations through innovations such as esports within the global basketball context. The primary objective of the study is to examine how basketball organizations leverage esports for international growth, in comparison with football-related esports development initiatives. A qualitative comparative approach is employed, drawing on document analysis and thematic coding. The investigation focuses on the esports projects of FIBA (International Basketball Federation), the NBA (National Basketball Association), and FIFA (International Football Federation), alongside their respective audience engagement strategies. The findings demonstrate that the football esports ecosystem is characterized by a well-defined structure, encompassing schools, clubs, and national federations that collaborate systematically to broaden audiences, enhance revenue generation, and strengthen other marketing communication indicators. Conversely, basketball esports systems – most notably, the NBA 2K League – exhibit a more centralized and geographically constrained framework, while lacking network-based institutional partnerships. Although FIBA has sought to establish a nationally grounded structure, the system remains fragmented and insufficiently stable. The study concludes that sustainable esports development requires an integrated ecosystem approach, drawing on the football sector’s experience, particularly through the incorporation of youth-oriented programs.